1998
DOI: 10.1159/000025610
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone and Calcitriol in Hypertension Caused by Dietary Calcium Deficiency in Rats

Abstract: Hypertension caused by calcium deficiency in the diet has been linked with an increase in parathyroid hormone (PTH) and calcitriol levels. We evaluated arterial blood pressure (ABP), PTH, and calcitriol in normotensive Sprague-Dawley rats (SDR) and in spontaneously hypertensive rats (SHR) fed from weaning on a control diet with a normal calcium content (1%) or a low-calcium diet (0.1%). The calcemia was also measured in the rats by colorimetric methods. The low-calcium diet decreased the calcemia in both strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
1
2
0
1
Order By: Relevance
“…In the present study, serum 1,25-D concentration was found as significantly increased in the MCF group compared with the con- [18,22]. When plasma calcium is decreased, the parathyroid glands are stimulated to produce PTH.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In the present study, serum 1,25-D concentration was found as significantly increased in the MCF group compared with the con- [18,22]. When plasma calcium is decreased, the parathyroid glands are stimulated to produce PTH.…”
supporting
confidence: 51%
“…When plasma calcium is decreased, the parathyroid glands are stimulated to produce PTH. In turn, increased PTH stimulates the upregulation of enzyme CYP27B1 in the kidney to form 1,25-D. Only when plasma calcium returns the normal levels, serum PTH secretion is depressed, and thus, 1,25-D synthesis is depressed [14,18]. In the present study, although serum 1,25-D was increased, serum PTH levels was not increased, quite the contrary serum PTH was significantly decreased in the MCF group compared with the controls (P<0.05).…”
mentioning
confidence: 99%
“…The administration of Ca is paradoxically associated with a decrease in arterial blood pressure, and different studies carried out by our research group have also demonstrated that Caenriched diets can control hypertension in rats (López-Miranda et al 1998;Civantos et al 1999;Civantos Calzada & Aleixandre de Artiñano, 2003;Civantos & Aleixandre, 2004). Dietary Ca supplements also have beneficial effects in hypertensive patients (for reviews see Pryer et al 1995;Allender et al 1996;Resnick, 1999).…”
mentioning
confidence: 82%
“…Varios grupos de investigación, y también el nuestro, han observado que antes de que se estabilice la presión arterial de las ratas SHR, existe un período inicial en la vida de estos animales en el que esta variable aumenta progresivamente de forma muy marcada, alcanzando la PAS y la PAD valores estables sólo cuando las ratas tienen al menos 10-11 semanas de vida (López-Miranda et al, 1998;Civantos et al, 1999). Como ya se ha indicado en los resultados, las ratas SHR de los grupos control negativo y testigo (las que bebían agua, y las que bebían la solución de clara de huevo sin hidrolizar, respectivamente) presentaron, en realidad, en nuestro estudio valores de PAS y de PAD estables entre las 10 y las 25 semanas de vida.…”
Section: Resultados Y Discusiónunclassified